Smartphone sebagai Media Edukasi pada Pasien Diabetes Mellitus: A Systematic Review - Ainul Mufidah; Ninuk Dian Kurniawati; Ika Yuni Widyawati (FORIKES, 2021)
Background: Type 2 diabetes (T2D) is associated with various health complications and health service visits, resulting in high costs for patients and the community. As a result, worldwide exponential growth of T2D has become a major issue. One strategy is to provide electronic (e-) health interventions. This intervention can reach many individuals in cost-effective and effective way to change behavior.Objective: To find out the development of smartphones as an educational medium in patients with type 2 diabetes mellitus. Method: This Systematic Review was based on Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). The database used in this study was Scopus, Proquest and Pubmed were limited to the last 5 years of publication from 2016 to 2020, full text article and in English. The keywords used were